Makna Lupus bagi Odapus: Perspektif Komunikasi Kesehatan Islam - Septa Agustina (JURNAL ILMIAH SYI'AR, 2020)
The meaning becomes one part of communication. The meaning comes from human interpretation and makes humans to contemplate the experiences that occur during their lives. The meaning of Lupus for Odapus (people with lupus) is the process of interpretation in Odapus against Lupus both positive and negative. This study aims to determine the meaning of lupus for Odapus. As for scientific writing, it uses a qualitative-fenomenolgy paradigm. The method used was in-depth interviews, observations and documentation. The results of data analysis conducted on the three informants that the meaning of pain for Odapus through intrapersonal communication becomes the main thing for them to get closer to Allah, especially in the view of Islamic health communication. Lupus experienced by odapus allows them to view life more positively and reflect on every mistake. The three Odapus informants interpreted lupus illness / illness in their lives as a gift from God Almighty (faith), changing a healthier lifestyle, can strengthen communication in life partners and give effect to Odapus behavior such as enthusiasm, optimism, healing, patience and prejudice towards God who wants to alleviate and erase all sins them as Odapus.